2012
DOI: 10.1097/inf.0b013e31823096a8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Escherichia coli O157 Infection and the Risk of Hemolytic Uremic Syndrome, Minnesota

Abstract: Individuals infected with O157 infection presenting with a more severe illness were at an increased risk of developing HUS. The use of bactericidal antibiotics, particularly β-lactams, to treat O157 infection was associated with the subsequent development of HUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 24 publications
3
84
0
8
Order By: Relevance
“…21 In this study, more than a fifth of the respondents use antibiotics indiscriminately in the treatment of diarrhoea which may be dangerous as some cases of enteroheamorrhagic Escherichia coli infection have been associated with increased risk of the development of haemolytic uremic syndrome after indiscriminate antibiotic treatment. [22][23] this study revealed that 72.4% of respondents use same antibiotics as previously prescribed by their doctor to treat their perceived infections. Self medication with antibiotics is defined as the acquisition and selfadministration of antibiotics with the aim of treating a perceived infection.…”
Section: Resultsmentioning
confidence: 99%
“…21 In this study, more than a fifth of the respondents use antibiotics indiscriminately in the treatment of diarrhoea which may be dangerous as some cases of enteroheamorrhagic Escherichia coli infection have been associated with increased risk of the development of haemolytic uremic syndrome after indiscriminate antibiotic treatment. [22][23] this study revealed that 72.4% of respondents use same antibiotics as previously prescribed by their doctor to treat their perceived infections. Self medication with antibiotics is defined as the acquisition and selfadministration of antibiotics with the aim of treating a perceived infection.…”
Section: Resultsmentioning
confidence: 99%
“…Piercefield et al used admission white blood cell count >20 000 cells/µL as a proxy for illness severity; however, adjustment did not change their results (adjusted values not provided) [20]. Smith et al adjusted for vomiting, fever, bloody diarrhea, and sex [25]. This minimally changed the ORs (1.…”
Section: Qualitative Review Of Results Adjusting For Covariatesmentioning
confidence: 99%
“…Although the lack of detail relating exposures to outcomes at a patient level limited some of our subanalyses, we did explore the relationships between country and acquisition (ie, outbreak vs sporadic). We additionally explored antibiotic class as a risk factor in our meta-analysis; no antibiotic/antibiotic class emerged as protective from the development of HUS, compared with nontreatment [25,27]. Although there are intra-and interserotype differences in the release of Shiga toxin from STEC after exposure to antibiotics in vitro [43], the decision to treat must be made at the time of initial presentation; hence, the variable release of toxin by an infecting strain cannot, for the foreseeable future, be entered into clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, most available data were obtained from retrospective and some prospective cohort studies demonstrating conflicting results. 5,9,13,[49][50][51][52][53][54] Prospective, blinded, and randomized studies have not been conducted, and observational studies have been affected by bias toward use of antibiotics in initially "sicker" patients. A number of metaanalyses and systematic reviews have attempted to summarize the results of available studies, reaching inconclusive results and stating that more prospective, appropriately powered studies are needed.…”
mentioning
confidence: 99%